2015
DOI: 10.1109/tmag.2015.2438064
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetism in Zn1–xMnxO Nanoparticles Prepared by Ball Milling

Abstract: code: FS-04 Previous studies pointed out that ferromagnetism in Mn-doped ZnO was related to exchange interactions between Mn ions mediated by lattice defects. This means that it is possible to modify a Mn-doped ZnO paramagnet to a ferromagnet by creating lattice defects in it. The present work starts from a paramagnetic Zn 0.98 Mn 0.02 O sample prepared by solid-state reaction, and then creates more defects upon mechanical milling. By changing the milling time (t m ) from 0.5 to 20 h, we produced nanocrystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…It has been shown that the condition for ferromagnetic ordering in NCs DMS is not only the fact of presence but also the corresponding structure of defects [3,4]. It has been established that such a structure of defects can be formed by milling of ZnO:Mn polycrystals in an inert medium [5]. Under such treatment, a defective nearsurface layer with a large number of oxygen vacancies (Vo) is formed in the nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the condition for ferromagnetic ordering in NCs DMS is not only the fact of presence but also the corresponding structure of defects [3,4]. It has been established that such a structure of defects can be formed by milling of ZnO:Mn polycrystals in an inert medium [5]. Under such treatment, a defective nearsurface layer with a large number of oxygen vacancies (Vo) is formed in the nanocrystals.…”
Section: Introductionmentioning
confidence: 99%